Pengantar editorial MediaPsi 9(1) 2023 - Akhrani, Lusy Asa (Mediapsi, 2023)
The contributions to this edition of MediaPsi are summarized in the opening paragraph. The articles in this issue of MediaPsi are based on psychological dynamics that take place throughout the lifespan of an individual. The first three articles present research findings on adolescents dealing with various phenomena, such as friendship and dating relationships and coping mechanisms for adolescents dealing with anxiety. The fourth article discusses the early adulthood period in the context of organizations and workers. The fifth article presents research findings on a variety of late adults and elderly who are in rehabilitation situations as beggars and homeless.